Markers of Inflammation, Oxidative Stress, and Fibrosis in Patients with Atrial Fibrillation. (23rd May 2022) - Pauklin, Priit; Zilmer, Mihkel; Eha, Jaan; Tootsi, Kaspar; Kals, Mart; Kampus, Priit
Abstract : Atrial fibrillation (AF) is the most common sustained cardiac arrhythmia in clinical practice. The pathogenesis of AF is linked to inflammatory reaction and oxidative stress, which leads to fibrosis of the atria and progression of the disease. The purpose of this study was to define the role of several biomarkers of inflammation, fibrosis, and oxidative stress (OxS). We included 75 patients with paroxysmal/persistent AF, who were admitted for electrical cardioversion or pulmonary vein isolation (PVI). High-sensitivity C-reactive protein (hsCRP), galectin-3 (Gal-3), myeloperoxidase (MPO), oxidized low-density lipoprotein (oxLDL), and N-terminal pro-brain natriuretic peptide (NT-proBNP) were measured before the procedures. We compared the results with those of 75 healthy age-, sex-, and blood pressure-matched individuals. The patients were followed up for 1 year after the intervention to establish the recurrence of AF and its association with the measured markers. Patients with AF had higher MPO (52.6 vs. 36.2 ng/ml, p < 0.001 ) and NT-proBNP (209.0 vs. 28.0 pg/ml, p < 0.001 ) compared to healthy subjects. Also, they showed significantly higher levels of hsCRP (1.5 vs. 1.1 mg/l, p = 0.001 ) and Gal-3 (11.4 vs. 9.7 mg/l, p = 0.003 ), while there was no difference found in oxLDL (71.5 vs. 71.7 U/l, p = 0.449 ). MPO (OR = 1.012, p = 0.014 ), hsCRP (OR = 1.265, p = 0.026 ), and weight (OR = 1.029, p = 0.013 ) were independently associated with AF in a multivariable logistic regression analysis. Patients with successful maintenance of sinus rhythm (SR) for one year had lower baseline MPO (40.5 vs. 84.3 ng/ml, p = 0.005 ) and NT-proBNP (127.5 vs. 694.0 pg/ml, p < 0.001 ) compared to patients with recurrent AF episodes, but there was no difference in hsCRP, Gal-3, or oxLDL between them. MPO (OR = 0.985, p = 0.010 ) was independently associated with AF recurrence during the follow-up period when adjusted for cofounders. Patients with AF had increased markers of inflammation and fibrosis, while there was no increase detected in the OxS marker oxLDL. MPO was independently associated with AF in a multivariate model. Inflammatory and fibrotic mechanisms are important factors in electrical and structural remodelling progress in the atria of patients with AF.